Transition zone impermeable material as well as preparation method and application thereof
By using transition zone anti-seepage materials of the resin film layer containing rosin-type materials, the problem of low connection reliability of HDPE geomembrane and TPO geomembrane is solved, and efficient welding strength and anti-seepage performance are achieved.
Patent Information
- Application Number
- CN202510314509.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-27
- Estimated Expiration
- 2045-03-17
AI Technical Summary
Due to poor compatibility when connecting HDPE geomembrane and TPO geomembrane, the connection reliability is low, and joint leakage problems are prone to affecting the quality of the project.
A transition zone anti-seepage material is used, which includes a resin film layer, which consists of polyethylene resin, polypropylene resin, olefin block copolymer resin, filler and flux. The flux includes rosin-type materials, which are connected to the HDPE geomembrane and the TPO geomembrane through welding technology.
It improves the connection reliability of HDPE geomembrane and TPO geomembrane, enhances welding strength, avoids joint leakage problems, and improves the anti-seepage reliability of the combined type geomembrane anti-seepage system.
Smart Images

Figure CN120209436A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of anti-seepage materials, and particularly relates to a transition zone anti-seepage material, a preparation method thereof, and an application thereof. Background Art
[0002] In large-scale water conservancy and hydropower anti-seepage projects (such as hydropower station reservoir basins, dam surfaces, water diversion and regulation channels, etc.), considering actual geological conditions and cost factors, different types of geomembrane anti-seepage systems need to be used in adjacent engineering parts. Commonly, HDPE geomembrane and TPO geomembrane are used as anti-seepage materials on the same working surface at the same time. In this case, the HDPE geomembrane and the TPO geomembrane need to be connected. However, due to factors such as poor compatibility between the HDPE geomembrane and the TPO geomembrane, the connection reliability between the two is poor. Specifically, whether the HDPE geomembrane and the TPO geomembrane are directly welded or bonded with an adhesive, the joint peel strength of the HDPE geomembrane and the TPO geomembrane is relatively low, usually not exceeding 3 N / mm, and problems such as joint leakage are likely to occur under actual service conditions, affecting the project quality. Summary of the Invention
[0003] The present invention provides a transition zone anti-seepage material, a preparation method thereof, and an application thereof. The transition zone anti-seepage material can improve the connection reliability between the HDPE geomembrane and the TPO geomembrane, and avoid problems such as joint leakage in the combined geomembrane anti-seepage system under actual service conditions.
[0004] In one aspect of the present invention, a transition zone anti-seepage material is provided. The transition zone anti-seepage material satisfies that in the curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane changing with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm; in the curve of the welding peel strength of the transition zone anti-seepage material and the TPO geomembrane changing with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm.
[0005] According to an embodiment of the present invention, in the curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane changing with displacement, in the interval where the displacement exceeds 50 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm; and / or, in the curve of the welding peel strength of the transition zone anti-seepage material and the TPO geomembrane changing with displacement, in the interval where the displacement exceeds 50 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm.
[0006] According to an embodiment of the present invention, the transition zone anti-seepage material includes a resin film layer. The resin film layer includes polyethylene resin, polypropylene resin, olefin block copolymer resin, filler, and flux. The flux includes rosin-based materials.
[0007] According to an embodiment of the present invention, the mass ratio of the polyethylene resin in the resin film layer is 25%-60%; and / or, the mass ratio of the polypropylene resin in the resin film layer is 12%-38%; and / or, the mass ratio of the olefin block copolymer resin in the resin film layer is 4%-26%; and / or, the mass ratio of the filler in the resin film layer is 10% to 40%; and / or, the mass ratio of the soldering flux in the resin film layer is 0.1% to 8%; and / or, the polyethylene resin includes one or more of high-density polyethylene, medium-density polyethylene, and linear low-density polyethylene; and / or, the density of the polyethylene resin is between 0.920-0.955 g / cm 3 and the melt index under the conditions of 190°C and 2.16 KG is between 0.15-4.0 g / 10 min; and / or, the polypropylene resin includes one or more of propylene / ethylene / butene terpolymerized polypropylene, propylene / ethylene copolymerized polypropylene, and homopolypropylene; and / or, the density of the polypropylene resin is between 0.850-0.930 g / cm 3 and the melt index under the conditions of 230°C and 2.16 KG is between 0.3-3.5 g / 10 min; and / or, the olefin block copolymer resin includes one or more of ethylene / α-octene block copolymer and propylene / ethylene block copolymer; the density of the ethylene / α-octene block copolymer is between 0.860-0.890 g / cm 3 and the melt index under the conditions of 190°C and 2.16 KG is between 0.3-5.0; the density of the propylene / ethylene block copolymer is between 0.870-0.910 g / cm 3 and the melt index under the conditions of 230°C and 2.16 KG is between 6.0-10.0; and / or, the filler includes one or more of calcium carbonate, talcum powder, calcined kaolin, and calcite; and / or, the rosin-based material includes one or more of polymerized rosin, rosin ester, and hydrogenated rosin; the transition zone anti-seepage material is the resin film layer, or the transition zone anti-seepage material further includes a support layer composite with the resin film layer, and the support layer includes non-woven fabric and / or mesh fabric.
[0008] According to an embodiment of the present invention, the resin film layer further includes an antioxidant, a light stabilizer, and a pigment. In terms of parts by mass, the mass parts of each component of the resin film layer are as follows: the polyethylene resin is 25-60 parts, the polypropylene resin is 12-38 parts, the olefin block copolymer is 4-26 parts, the filler is 10-40 parts, the soldering flux is 0.1-8 parts, the antioxidant is 0.1-2 parts, the light stabilizer is 0.1-2 parts, and the pigment is 0.1-5 parts.
[0009] According to an embodiment of the present invention, the antioxidant includes organic phosphite and / or hindered phenol antioxidant; and / or, the light stabilizer includes hindered amine light stabilizer; and / or, the pigment includes one or more of titanium dioxide (TiO2), carbon black, iron oxide, Prussian blue, lead silicate, monoazo, bisazo, and phthalocyanine.
[0010] According to an embodiment of the present invention, the hardness of the transition zone anti-seepage material is less than the hardness of the HDPE geomembrane and greater than the hardness of the TPO geomembrane; and / or, the hardness of the transition zone anti-seepage material is between 40-55 Shore D; and / or, the transition zone anti-seepage material is a sealing edge electrode or a transition zone anti-seepage membrane.
[0011] On the other hand, the present invention provides a method for preparing the above-mentioned transition zone anti-seepage material, including the following steps: extruding and molding the material for forming the resin layer to form the resin layer, thereby obtaining the transition zone anti-seepage material.
[0012] According to an embodiment of the present invention, the process of extruding and molding the material for forming the resin layer includes: extruding and molding the material for forming the resin layer through a twin-screw extruder to form the resin layer, thereby obtaining the transition zone anti-seepage material; or, the process of extruding and molding the material for forming the resin layer includes: extruding and pelletizing the material for forming the resin layer through a twin-screw extruder, and then extruding and molding the obtained pellets through a single-screw extruder to form the resin layer, thereby obtaining the transition zone anti-seepage material; and / or, the transition zone anti-seepage material further includes a support layer compounded with the resin layer, and the support layer includes non-woven fabric and / or mesh fabric; the preparation process of the transition zone anti-seepage material further includes the process of compounding the resin layer with the support layer.
[0013] On the other hand, the present invention provides an application of the above-mentioned transition zone anti-seepage material in welding HDPE geomembrane and TPO geomembrane.
[0014] The transition zone anti-seepage material provided by the present invention, its preparation method and application. The transition zone anti-seepage material can simultaneously improve the welding strength between the transition zone anti-seepage material and the HDPE geomembrane (in the curve of the peel strength of the transition zone anti-seepage material and the HDPE geomembrane varying with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm), and the welding strength between the transition zone anti-seepage material and the TPO geomembrane (in the curve of the peel strength of the transition zone anti-seepage material and the TPO geomembrane varying with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm). This transition zone anti-seepage material can be used as a welding material to connect the HDPE geomembrane and the TPO geomembrane, enabling a strong bonding degree between the HDPE geomembrane and the TPO geomembrane, and preventing problems such as opening or rupture at the connection part (seam) between them. It can effectively avoid problems such as seam leakage in the combined geomembrane anti-seepage system under actual service conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 FIG. is a schematic structural diagram of a combined geomembrane anti-seepage system formed by welding an HDPE geomembrane and a TPO geomembrane using a transition zone anti-seepage material according to an embodiment of the present invention;
[0016] Figure 2 FIG. is a schematic structural diagram of a combined geomembrane anti-seepage system formed by welding an HDPE geomembrane and a TPO geomembrane using a transition zone anti-seepage material according to another embodiment of the present invention;
[0017] Figure 3 FIG. is a graph of the weld peel strength curve of the transition zone anti-seepage membrane material and the TPO geomembrane or HDPE geomembrane in Example 1 and the weld peel strength curve of the TPO geomembrane and the HDPE geomembrane in Comparative Example 1;
[0018] Figure 4 FIG. is a graph of the weld peel strength curve of the transition zone anti-seepage membrane material and the HDPE geomembrane in Example 1 and Comparative Example 2;
[0019] Figure 5 FIG. is a graph of the weld peel strength curve of the transition zone anti-seepage membrane material and the TPO geomembrane in Example 1 and Comparative Example 3;
[0020] Figure 6 FIG. is a graph of the weld peel strength curve after edge sealing and pressure welding of the HDPE geomembrane and the TPO geomembrane using an edge sealing electrode in Example 1 and the weld peel strength curve of the TPO geomembrane and the HDPE geomembrane in Comparative Example 1.
[0021] Description of reference numerals: 1: HDPE geomembrane; 2: TPO geomembrane; 3: anti-seepage material for transition zone; 300: body part; 301: first connection part; 302: second connection part; 303: third connection part, third welding part; 4: fourth connection part; x: first direction; y: second direction. Detailed implementation manners
[0022] To enable those skilled in the art to better understand the solution of the present invention, the present invention will be further described in detail below. The specific implementation manners listed below only describe the principles and features of the present invention, and the examples given are only used to explain the present invention, not to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation manners obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.
[0023] In large-scale water conservancy and hydropower anti-seepage projects (such as hydropower station reservoir basins, dam surfaces, water diversion and regulation channels, etc.), considering the actual geological conditions and cost factors, it is usually necessary to use HDPE geomembrane and TPO geomembrane as anti-seepage materials on the same working surface. In this case, it is necessary to connect the high-density polyethylene (HDPE) geomembrane and the thermoplastic polyolefin (TPO) geomembrane. Generally, rigid anchoring connection, bonding through adhesives, and welding can be carried out. However, these connection methods generally have problems of poor connection reliability, and are prone to problems such as joint leakage under actual service conditions, affecting the project quality.
[0024] Specifically, for the rigid anchoring connection, mainly a concrete structure is constructed between the HDPE geomembrane and the TPO geomembrane to rigidly anchor the joints of the two on the concrete structure, and then an elastic edge-sealing agent is used for edge-sealing treatment. This connection method has complex procedures, and the rigid anchoring is a destructive anchoring. There is a penetration channel between the anchor and the geomembrane. At the same time, due to the large stiffness difference between the geomembrane and the concrete, and the different thermal expansion and contraction effects of the materials, the elastic edge-sealing agent has poor effects in actual edge-sealing treatment, and is prone to situations such as opening or entire sheet falling off, resulting in leakage at the rigid anchoring.
[0025] For the method of bonding the HDPE geomembrane and the TPO geomembrane through an adhesive, due to factors such as their weak polarity and low surface energy, the bonding effect with common adhesives is not good, and the peel strength of the bonding joint is low (≤3 N / mm), which is less than the body strength of either of them. The joint is prone to being pulled apart due to factors such as the pressure of the water storage body or the settlement of the base layer during actual service, resulting in leakage.
[0026] Regarding the method of welding HDPE geomembrane and TPO geomembrane, it is usually to directly weld the HDPE geomembrane and TPO geomembrane. However, although the HDPE geomembrane and TPO geomembrane each have weldability, due to factors such as their different materials, their compatibility is poor, and reliable welding cannot be carried out between them. Whether it is a single-seam welding or double-seam welding form, the weld strength formed after direct welding of the two is low (weld peel strength ≤ 3 N / mm), which is less than the body strength of either of the two, and problems such as peel failure are likely to occur. During actual service, it is easily pulled apart due to factors such as water storage pressure or foundation settlement, resulting in leakage.
[0027] Therefore, how to improve the connection reliability of HDPE geomembrane and TPO geomembrane, improve the anti-seepage reliability of the combined geomembrane anti-seepage system formed by connecting HDPE geomembrane and TPO geomembrane, and avoid problems such as joint leakage during its use is a technical problem urgently to be solved in this field.
[0028] In view of this, the embodiment of the present invention provides a transition zone anti-seepage material, and the transition zone anti-seepage material satisfies: in the curve of the weld peel strength of the transition zone anti-seepage material and the HDPE geomembrane changing with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment with a peel strength greater than or equal to 6 N / mm; and in the curve of the weld peel strength of the transition zone anti-seepage material and the TPO geomembrane changing with displacement, in the interval where the displacement exceeds 30 mm, there is a curve segment with a peel strength greater than or equal to 6 N / mm.
[0029] For the transition zone anti-seepage material of the embodiment of the present invention, in the curve of the weld peel strength of the transition zone anti-seepage material and the HDPE geomembrane changing with displacement, even in the interval where the displacement exceeds 30 mm, there is still a curve segment with a peel strength greater than or equal to 6 N / mm, and in the curve of the weld peel strength of the transition zone anti-seepage material and the TPO geomembrane changing with displacement, even in the interval where the displacement exceeds 30 mm, there is still a curve segment with a peel strength greater than or equal to 6 N / mm. Thus, the weld strength between the transition zone anti-seepage material and the HDPE geomembrane, as well as the weld strength between the transition zone anti-seepage material and the TPO geomembrane can be improved simultaneously. This transition zone anti-seepage material can be used to weld the HDPE geomembrane and TPO geomembrane, reduce the problem of false welding, make the combination degree between the HDPE geomembrane and TPO geomembrane stronger, and it is not easy to have problems such as opening or rupture at the connection part (joint) of the two, and can effectively avoid problems such as joint leakage in the actual service conditions of the combined geomembrane anti-seepage system.
[0030] Exemplarily, in the curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane varying with displacement, for example, in the intervals where the displacement exceeds 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm, 200mm, there are curve segments with a peel strength greater than or equal to 6N / mm, or in the intervals defined by the ranges composed of any two of the foregoing values, there are curve segments with a peel strength greater than or equal to 6N / mm.
[0031] Exemplarily, in the curve of the welding peel strength of the transition zone anti-seepage material and the TPO geomembrane varying with displacement, for example, in the intervals where the displacement exceeds 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm, 200mm, there are curve segments with a peel strength greater than or equal to 6N / mm, or in the intervals defined by the ranges composed of any two of the foregoing values, there are curve segments with a peel strength greater than or equal to 6N / mm.
[0032] In some embodiments, in the curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane varying with displacement, in the interval where the displacement exceeds 50mm, there may be a curve segment with a peel strength greater than or equal to 6N / mm. In the curve of the welding peel strength of the transition zone anti-seepage material and the TPO geomembrane varying with displacement, in the interval where the displacement exceeds 50mm, there is a curve segment with a peel strength greater than or equal to 6N / mm, which is more conducive to the transition zone anti-seepage material being applicable to welding the HDPE geomembrane and the TPO geomembrane, reducing the problem of false welding, enabling a stronger bonding degree between the HDPE geomembrane and the TPO geomembrane, and making it less likely to have problems such as opening or rupture at the connection part (seam) between the two, effectively avoiding problems such as joint leakage in the combined type geomembrane anti-seepage system under actual service conditions.
[0033] In the embodiment of the present invention, the impermeable material 3 of the transition zone may include a resin film layer, and the resin film layer includes a resin material, which may include polyethylene resin, polypropylene resin (flexible polypropylene), olefin block copolymer resin, filler, and flux. Under such an impermeable material system of the transition zone, the impermeable material 3 of the transition zone contains both polyethylene resin and polypropylene resin, and an olefin block copolymer resin is introduced to compatibilize and modify the blend system of the polyethylene resin and the polypropylene resin. By utilizing the properties such as the block characteristics of the compatibilizing resin (olefin block copolymer resin), the thermal adhesion of the impermeable material 3 of the transition zone to the HDPE and TPO geomembranes 2 is improved, which is more conducive to the impermeable material 3 of the transition zone having good compatibility with both the HDPE geomembrane 1 and the TPO geomembrane 2, improving the welding strength of the impermeable material 3 of the transition zone with the HDPE geomembrane 1, and at the same time improving the welding strength of the impermeable material 3 of the transition zone with the TPO geomembrane 2, as well as improving the welding strength when using the impermeable material 3 of the transition zone as a sealing edge electrode to seal the edges of the HDPE geomembrane 1 and the TPO geomembrane 2, further improving the connection reliability of the HDPE geomembrane 1 and the TPO geomembrane 2. At the same time, a rosin-based material containing a tricyclic phenanthrene skeleton is incorporated, which has hydrophobic properties and can construct an impermeable material for the transition zone suitable for a long-term immersion environment. Meanwhile, fillers are introduced into the impermeable material of the transition zone for filling, which can increase the surface roughness of the impermeable material of the transition zone. At the same time, the rosin-based material has a low surface energy. By mixing the rosin with a low surface energy, the surface tension of the impermeable material of the transition zone can be reduced, and the wettability of the impermeable material of the transition zone to geomembranes such as the HDPE geomembrane 1 during the welding process can be increased, thereby improving the welding strength and reliability of the impermeable material of the transition zone with geomembranes such as the HDPE geomembrane 1.
[0034] Specifically, the olefin block copolymer resin includes one or more of ethylene / α-octene block copolymer and propylene / ethylene block copolymer (OBC), further improving the compatibility of the blend system of the polyethylene resin and the polypropylene resin, as well as the compatibility of the impermeable material 3 of the transition zone with both the HDPE geomembrane 1 and the TPO geomembrane 2, and improving the connection reliability of the HDPE geomembrane 1 and the TPO geomembrane 2.
[0035] In addition, according to the inventors' research, if an olefin copolymer with a polar group (such as maleic anhydride grafted polyethylene / polypropylene, ethylene-methyl acrylate copolymer, etc.) is used to compatibilize and modify a blend system of copolymerized polyethylene and copolymerized polypropylene, or polyethylene and homopolypropylene, the introduction of the polar group will reduce the long-term immersion stability of the material, resulting in water absorption and swelling. By further using the above-mentioned olefin block copolymer combination without a polar group to compatibilize and modify the blend system of polyethylene resin and flexible polypropylene, while improving the connection reliability between the HDPE geomembrane 1 and the TPO geomembrane 2, the system of the transition zone anti-seepage material 3 can be made stable and durable, adaptable to a long-term immersion environment, not prone to water absorption and swelling, and further improving the anti-seepage reliability of the combined geomembrane anti-seepage system.
[0036] In some embodiments, the density of the ethylene / α-octene block copolymer can be between 0.860 and 0.890 g / cm 3 and the melt index (melt index (190 °C / 2.16 KG)) at 190 °C and 2.16 KG can be between 0.3 and 5.0.
[0037] In some embodiments, the density of the propylene / ethylene block copolymer can be between 0.870 and 0.910 g / cm 3 preferably between 0.87 and 0.88 g / cm 3 and the melt index (melt index (230 °C / 2.16 KG)) at 230 °C and 2.16 KG can be between 6.0 and 10.0, preferably between 6.0 and 7.0 g / 10 min.
[0038] For example, the above-mentioned olefin block copolymer resin can be Infuse and Intune series resins of Dow Chemical, such as Infuse 9100 (ethylene / α-octene block copolymer), Intune d5535 (propylene / ethylene block copolymer), etc.
[0039] In some embodiments, the mass ratio of the polyethylene resin in the resin film layer can be 25%-60%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc.
[0040] In some embodiments, the mass ratio of the polypropylene resin in the resin film layer can be 12%-38%, such as 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35% or 38%, etc.
[0041] And / or, the mass ratio of the olefin block copolymer resin in the resin film layer can be 4%-26%, such as 4%, 7%, 10%, 13%, 16%, 19%, 21%, 23 or 26%, etc.
[0042] Specifically, the polyethylene resin may include one or more of high density polyethylene (HDPE), medium density polyethylene (MDPE), and linear low density polyethylene (LLDPE).
[0043] Specifically, the density of the polyethylene resin may be between 0.920 and 0.955 g / cm 3 and the melt index (i.e., MFR (190°C / 2.16 kg)) at 190°C and 2.16 kg condition may be between 0.15 and 4.0 g / 10 min.
[0044] For example, the polyethylene resin may be DGDA 6094 (high density polyethylene) of Fujian United Petrochemical, TR144 (high density polyethylene) of Sinopec, Enable4009MC (medium density polyethylene) of ExxonMobil, mPE E332H (medium density polyethylene) of Sinopec, Exceed S 9243ML (linear low density polyethylene) of ExxonMobil, etc.
[0045] In some preferred embodiments, the medium density polyethylene may specifically include metallocene-catalyzed medium density polyethylene, and its density may be between 0.93 and 0.94 g / cm 3 such as Enable4009MC (medium density polyethylene) of ExxonMobil, mPE E332H (medium density polyethylene) of Sinopec, etc.
[0046] In addition, the polypropylene resin may include one or more of propylene / ethylene / butene terpolymer polypropylene (C3 / C2 / C4 terpolymer polypropylene (reactive grade TPO)), propylene / ethylene copolymer polypropylene (C3 / C2 copolymer polypropylene), and homopolypropylene.
[0047] Specifically, the density of the polypropylene resin may be between 0.850 and 0.930 g / cm 3 and the melt index (MFR (230°C / 2.16 kg)) at 230°C and 2.16 kg condition may be between 0.3 and 3.5 g / 10 min.
[0048] For example, the polypropylene resin may be Hifax CA 10A (reactive grade TPO) of LyondellBasell, Versify 2300 of Dow Chemical, Vistamaxx 6102 (C3 / C2 copolymer polypropylene) of ExxonMobil, B9302 (C3 / C2 copolymer polypropylene) of Sinopec, M02d (homopolypropylene) of Sinopec, etc.
[0049] In some preferred embodiments, the polypropylene resin includes a reactive grade TPO, the density of which can be between 0.87 - 0.89 g / cm 3 and the melt index (230 °C / 2.16 KG) can be between 0.3 - 1.0 g / 10 min. For example, the polypropylene resin can be Hifax CA 10A (reactive grade TPO) from LyondellBasell.
[0050] In some embodiments, the mass ratio of the filler to the resin film layer is 10% - 40%, such as 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc. By filling the filler within the above dosage range in the transition zone impervious material 3, the surface roughness of the transition zone impervious material 3 can be increased. Combining with the low surface energy rosin-like material, the surface tension can be reduced, and the wettability of the transition zone impervious material on the surface of geomembranes such as HDPE geomembrane during the welding process can be increased, further improving the welding strength and reliability between the transition zone material and the HDPE geomembrane 1 and the TPO geomembrane 2.
[0051] Specifically, the filler can include one or more of calcium carbonate, talcum powder, calcined kaolin, and calcite. Among them, ultrafine active heavy calcium carbonate is preferred, and its bulk density is between 1 - 1.3 g / cm 3 and the average particle size (D50) is between 4.0 - 6.0 μm. For example, Omyacarb 6 from Omya is used.
[0052] In some embodiments, the mass ratio of the flux to the resin film layer is 0.1% - 8%, such as 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%, etc. By introducing the flux (rosin-like material) within this content range into the transition zone impervious material, it is more conducive to exerting the hydrophobic function and low surface energy properties of the rosin-like material, improving the water resistance of the transition zone impervious material, and at the same time increasing the wettability of the transition zone impervious material on the surface of geomembranes such as HDPE geomembrane during the welding process, further improving the welding strength and reliability between the transition zone material and the HDPE geomembrane 1 and the TPO geomembrane 2.
[0053] In some embodiments, the flux (rosin-like material) can include one or more of polymerized rosin, rosin ester, and hydrogenated rosin, which is more conducive to the synergistic cooperation of the flux with components such as olefin block copolymer and filler, exerting the hydrophobic function and low surface energy properties of the rosin-like material, improving the water resistance of the transition zone impervious material, and at the same time increasing the wettability of the transition zone impervious material on the surface of geomembranes such as HDPE geomembrane during the welding process, further improving the welding strength and reliability between the transition zone material and the HDPE geomembrane 1 and the TPO geomembrane 2.
[0054] In some preferred embodiments, the flux includes polymerized rosin and hydrogenated rosin, and the mass ratio of the two can be 1:(0.8 - 1.2), for example, about 1:1.
[0055] In the embodiments of the present invention, the rosin materials used can be obtained by conventional methods in the art, such as commercially purchased or self-made by conventional methods in the art. For example, the polymerized rosin can be POLY-PALE of Eastman, the rosin ester can be Sylvalite RE 105L of Kraton, and the hydrogenated rosin can be AX-E of Eastman, etc.
[0056] In addition, the transition zone anti-seepage material 3 may further include one or more of an oxidant, a light stabilizer, and a pigment.
[0057] Specifically, the antioxidant may include an organic phosphite and / or a hindered phenol antioxidant, and specifically, it can be a compound system of a low-volatility hydrolysis-resistant organic phosphite and a hindered phenol antioxidant, such as Irganox B 225 of BASF.
[0058] Specifically, the light stabilizer may include a hindered amine type light stabilizer, and specifically, it can be a block oligomeric hindered amine type light stabilizer, such as Chimassorb 2020 of BASF.
[0059] Specifically, the pigment may include one or several of titanium dioxide (TiO2), carbon black, iron oxide, Prussian blue, lead silicate, monoazo, bisazo, and phthalocyanine. Among them, the titanium dioxide (titanium white) may include rutile type TiO2, such as LR-972 of Longmang Titanium Industry.
[0060] In some embodiments, the mass ratio of the antioxidant in the resin film layer can be 0.1% - 2%, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8% or 2%, etc.
[0061] In some embodiments, the mass ratio of the light stabilizer in the resin film layer can be 0.1% - 2%, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8% or 2%, etc.
[0062] In some embodiments, the mass ratio of the pigment in the resin film layer can be 0.1% - 5%, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4% or 5%, etc.
[0063] In some specific embodiments, by mass parts, the mass parts of each component of the resin film layer are as follows: 25 - 60 parts of polyethylene resin, 12 - 38 parts of polypropylene resin, 4 - 26 parts of olefin block copolymer, 10 - 40 parts of filler, 0.1 - 8 parts of soldering flux, 0.1 - 2 parts of antioxidant, 0.1 - 2 parts of light stabilizer, and 0.1 - 5 parts of pigment.
[0064] In the embodiments of the present invention, the transition zone anti-seepage material 3 can be the above resin film layer (i.e., the transition zone anti-seepage material 3 is a homogeneous transition zone anti-seepage material), or the transition zone anti-seepage material 3 can further include a support layer compounded with the above resin layer (i.e., the transition zone anti-seepage material is a composite transition zone anti-seepage material). The support layer can include non-woven fabric and / or mesh fabric. The mesh fabric can include fiber mesh fabric, that is, the forming material of the mesh fabric can include fiber material, and the fiber material can specifically include polyester fiber and / or glass fiber (glass fiber).
[0065] Specifically, when the transition zone anti-seepage material 3 further includes a support layer, at least one side of the support layer has the above resin layer. For example, one side of the support layer has a resin layer. At this time, the transition zone anti-seepage material 3 is composed of a resin layer and a support layer, and the support layer is located on the back of the resin layer. The transition zone anti-seepage material 3 is a back-lined transition zone anti-seepage material; or, both opposite sides of the support layer have resin layers, that is, the transition zone anti-seepage material 3 includes two resin layers and a support layer located between the two resin layers.
[0066] In some specific embodiments, the support layer is non-woven fabric, and one side of the non-woven fabric has a resin layer (i.e., the transition zone anti-seepage material 3 is a composite (back-lined) transition zone anti-seepage material).
[0067] In some other specific embodiments, the support layer is mesh fabric, and both opposite sides of the mesh fabric have resin layers, that is, the transition zone anti-seepage material 3 includes two resin layers and a mesh fabric located between the two resin layers.
[0068] In addition, the transition zone anti-seepage material 3 can be strip-shaped or film-shaped. Specifically, the transition zone anti-seepage material 3 can be used as a sealing edge welding rod (strip-shaped) and applied to the lap edge of the HDPE geomembrane 1 and the TPO geomembrane 2 (as Figure 2 shown); or, the transition zone anti-seepage material 3 can be a transition zone anti-seepage membrane (film-shaped, or called transition zone anti-seepage membrane material). When the transition zone anti-seepage material 3 is connected between the HDPE geomembrane 1 and the TPO geomembrane 2 as a transition zone anti-seepage membrane material (as Figure 1 shown), the transition zone anti-seepage material 3 can be lap-edge welded to the HDPE geomembrane 1 and the TPO geomembrane 2 respectively.
[0069] An embodiment of the present invention also provides a method for preparing the above-mentioned transition zone anti-seepage material 3, which includes the following steps: extruding the material for forming the resin layer to form the resin layer, thereby obtaining the transition zone anti-seepage material 3.
[0070] Specifically, during the extrusion molding process, a suitable mold can be used to form a resin layer with a preset shape, thereby obtaining a transition zone anti-seepage material 3 with a preset shape. For example, when forming a strip-shaped transition zone anti-seepage material (sealing edge welding rod) 3, a round hole mold can be used for extrusion molding to obtain the strip-shaped transition zone anti-seepage material 3; when forming a film-shaped transition zone anti-seepage material 3, a flat extrusion mold can be used for extrusion molding to obtain the film-shaped transition zone anti-seepage material 3.
[0071] In some embodiments, as described above, the transition zone anti-seepage material further includes a support layer compounded with the resin layer. The support layer can include non-woven fabric and / or mesh fabric. The preparation process of the transition zone anti-seepage material further includes the process of compounding the resin layer with the support layer.
[0072] In an embodiment of the present invention, the resin layer and the support layer can be compounded by hot pressing to obtain the transition zone anti-seepage material 3. Specifically, during the preparation process of the transition zone anti-seepage material 3, a twin-screw extruder and / or a single-screw extruder can be used for extrusion. Subsequently, the extruded material can be hot-pressed and compounded with the support layer to obtain the transition zone anti-seepage material 3.
[0073] In an embodiment of the present invention, the resin layer can be formed by a one-step forming method or a two-step forming method to prepare the transition zone anti-seepage material 3 (such as a transition zone anti-seepage membrane material or a transition zone material for forming a sealing edge welding rod).
[0074] In some embodiments, the resin layer is formed by a one-step forming method, that is, the process of extruding the material for forming the resin layer includes: extruding the material for forming the resin layer through a twin-screw extruder to form the resin layer, thereby obtaining the transition zone anti-seepage material 3.
[0075] Specifically, during the preparation process of the one-step forming method, after uniformly mixing the resin material with other materials (powder materials), it is extruded through a twin-screw extruder to directly form a transition zone anti-seepage material 3 with a preset shape. Among them, when preparing the transition zone anti-seepage membrane material, a flat extrusion mold is used during extrusion through the twin-screw extruder to form a film-shaped transition zone anti-seepage membrane material; when preparing the transition zone material for forming a sealing edge welding rod, a round hole mold can be used during extrusion through the twin-screw extruder to obtain the transition zone material. Among them, when the transition zone anti-seepage membrane material includes a support layer, the film material extruded from the twin-screw extruder can be hot-pressed and compounded with the support layer to obtain the transition zone anti-seepage material 3.
[0076] For example, the process of forming a resin layer by one-step forming method may include: using a high-speed mixer to uniformly mix resin pellets (resin material) and powder respectively, and using a twin-screw extruder for shear co-blending extrusion (using a flat extrusion die), wherein the resin pellets are fed from the feeding port at the starting end of the screw, and the powder is fed from the side feeding port; subsequently: (a) when the transition zone anti-seepage membrane material does not include a support layer, the sheet extruded from the die directly enters a three-roll calender for thickness fixing, and then is trimmed, length-fixed and cut, wound and packaged to obtain the transition zone anti-seepage membrane material (homogeneous transition zone anti-seepage membrane material); (b) when the transition zone anti-seepage membrane material includes a support layer, the process of thermocompression bonding the support layer and the resin layer may include: unwinding the support layer from the back of the three rolls and winding it to the front of the three rolls, entering the middle and lower rolls together with the raw material extruded from the die for thermocompression bonding and thickness fixing, and then trimming, length-fixed and cut, and winding to obtain the composite membrane material after the resin layer and the support layer are composite.
[0077] Wherein, when one side of the support layer (such as non-woven fabric) has a resin layer, step (b) is carried out once to composite the resin layer on one side of the support layer, and the obtained composite membrane material is the transition zone anti-seepage material (composite (backing type) transition zone anti-seepage membrane material) 3.
[0078] When both sides of the support layer (such as grid cloth) have resin layers (hereinafter, the two sides of the support layer are respectively denoted as the first side and the second side), step (b) is carried out once first to composite the resin layer on the first side of the support layer. Subsequently, the obtained composite membrane material is unwound and reversed, and step (b) is repeated (that is, the composite membrane material is unwound from the back of the three rolls and wound to the front of the three rolls, enters the middle and lower rolls together with the raw material extruded from the die for thermocompression bonding and thickness fixing, and then is trimmed, length-fixed and cut, and wound) to composite the resin layer on the second side of the composite membrane material to obtain the composite transition zone anti-seepage material 3.
[0079] After the transition zone anti-seepage material 3 is obtained through the above preparation process, the transition zone anti-seepage material 3 can be processed such as packaged as needed, and no special limitation is made thereto.
[0080] In the above preparation process, during the process of forming the resin layer by one-step forming method, the barrel temperature of the twin-screw extruder can be set to 165-195 °C, such as 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C or the range composed of any two of them, specifically to ensure that the melt temperature does not exceed 230 °C.
[0081] In addition, the process of preparing the edge-sealing welding rod by one-step forming method may include: uniformly mixing the resin pellets and powder in the formula respectively with a high-speed mixer, and performing shear blending and extrusion granulation using a twin-screw extruder (adopting a round-hole die to form an extruded product (strip) in the shape of an edge-sealing welding rod), wherein the resin pellets are fed from the feeding port at the starting end of the screw, and the powder is fed from the side feeding port; the strip extruded from the die opening is cooled by circulating water in a water tank, traction, air drying, fixed-length cutting, drying, and collection to obtain the transition zone material for forming the edge-sealing welding rod; wherein, the barrel temperature of the twin-screw extruder can be set at 165 - 195 °C to ensure that the melt temperature does not exceed 230 °C; the diameter of the transition zone material for forming the edge-sealing welding rod is controlled at about 3 - 4 mm by controlling the ratio of the extrusion amount to the traction speed.
[0082] After obtaining the transition zone material for forming the edge-sealing welding rod, the welding rod can be extruded by a handheld extrusion welding gun to perform extrusion edge sealing on the overlapping area of the HDPE geomembrane 1 and the TPO geomembrane 2.
[0083] In some other embodiments, the resin layer is formed by a two-step forming method, that is, the material for forming the resin layer is extruded and granulated by a twin-screw extruder, and then the obtained pellets are extruded and formed by a single-screw extruder to form the resin layer, thus obtaining the transition zone anti-seepage material 3.
[0084] Specifically, in the process of preparing the transition zone anti-seepage material 3 by the two-step forming method, first, the resin material (resin pellets) and other materials (powder) are uniformly mixed, and after being extruded and granulated by a twin-screw extruder, the obtained mixed pellets are transferred to a single-screw extruder for extrusion forming. This preparation process is mainly used for preparing the transition zone anti-seepage membrane material. Wherein, when the transition zone anti-seepage membrane material includes a support layer, the membrane material extruded from the twin-screw extruder can be hot-pressed and compounded with the support layer to obtain the transition zone anti-seepage material 3.
[0085] Among them, in the process of forming the resin layer by the two-step forming method, the barrel temperature of the twin-screw extruder can be 165 - 195 °C, such as 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C or the range composed of any two of them. Specifically, it can ensure that the melt temperature does not exceed 230 °C.
[0086] In addition, in the process of forming the resin layer by the two-step forming method, the barrel temperature of the single-screw extruder can be 175 - 190 °C, such as 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C or the range composed of any two of them, and the die temperature can be 180 - 185 °C.
[0087] Specifically, the process of preparing the transition zone anti-seepage membrane material by the two-step forming method may include:
[0088] S1: Use a high-speed mixer to uniformly mix the resin pellets and powders respectively, and perform shear blending and extrusion granulation using a twin-screw extruder (with a round-hole die). Among them, the resin pellets are fed through the feeding port at the starting end of the screw, and the powders are fed through the side feeding port; the strip extruded from the die opening is cooled by circulating water in a water tank, pulled, air-dried, granulated, dried, homogenized, and collected to obtain mixed pellets; the barrel temperature of the twin-screw extruder is set at 165 - 195 °C to ensure that the melt temperature does not exceed 230 °C;
[0089] S2: (a) Prepare the homogeneous transition zone anti-seepage material 3: Transfer the formulated pellets collected in S1 to a single-screw extruder, feed through the feeding port at the starting end of the screw, and after being conveyed by the screw, extruded and formed by the die, calendered and thickness-fixed by three rolls, trimmed, cut to a fixed length, wound, and packaged to obtain the homogeneous transition zone anti-seepage material 3 (i.e., the homogeneous transition zone anti-seepage membrane material); among them, the barrel temperature of the single-screw extruder is set at 175 - 190 °C, and the die temperature is set at 180 - 185 °C; (b) Prepare the composite transition zone anti-seepage material 3: Transfer the mixed pellets collected in S1 to a single-screw extruder, feed through the feeding port at the starting end of the screw, and at the same time, the support layer is unrolled from the back of the three rolls and wound to the front of the three rolls, and enters between the middle and lower rolls together with the raw material extruded from the die for hot pressing and compounding and thickness-fixing, and then through trimming, cut to a fixed length, and wound to obtain the composite membrane material after the resin layer and the support layer are compounded; among them, the barrel temperature of the single-screw extruder is set at 175 - 190 °C, and the die temperature is set at 180 - 185 °C.
[0090] Among them, when one side of the support layer (such as non-woven fabric) has a resin layer, perform step (b) once to compound a resin layer on one side of the support layer, and the obtained composite membrane material is the composite transition zone anti-seepage material (composite (backing type) transition zone anti-seepage membrane material) 3.
[0091] When both opposite sides of the support layer (such as grid cloth) have resin layers (hereinafter, the two opposite sides of the support layer are respectively denoted as the first side and the second side), first perform step (b) once to compound a resin layer on the first side of the support layer, and then unroll and reverse the obtained composite membrane material, and repeat step (b) (that is, transfer the mixed pellets collected in S1 to a single-screw extruder, feed through the feeding port at the starting end of the screw, and at the same time, this composite membrane material is unrolled from the back of the three rolls and wound to the front of the three rolls, and enters between the middle and lower rolls together with the raw material extruded from the die for hot pressing and compounding and thickness-fixing, and then through trimming, cut to a fixed length, and wound) to compound a resin layer on the second side of this composite membrane material to produce the composite transition zone anti-seepage material 3.
[0092] After obtaining the transition zone anti-seepage material 3 through the above preparation process, the transition zone anti-seepage material 3 can be processed such as packaged according to needs, and there is no special restriction on this.
[0093] In the embodiments of the present invention, unless otherwise specified, equipment or components such as twin-screw extruders, single-screw extruders, rollers, etc. can be conventional equipment or components in the art. Processes such as circulating water cooling, air drying, fixed-length cutting, drying, collection, as well as three-roll calendering for thickness determination, edge trimming, winding, packaging, etc. are all conventional operations in the art, and no special restrictions are imposed on this.
[0094] In the embodiments of the present invention, the powder refers to other materials other than the resin material used to form the resin layer. As described above, the resin materials include polyethylene resin, polypropylene resin, and olefin block copolymer resin. The powder includes fillers and soldering fluxes. In addition, the powder can also include antioxidants, light stabilizers, pigments, etc.
[0095] The embodiments of the present invention also provide an application of the above-mentioned transition zone anti-seepage material 3 in welding the HDPE geomembrane 1 and the TPO geomembrane 2.
[0096] When the transition zone anti-seepage material in the embodiments of the present invention is applied, the transition zone anti-seepage material can be welded between the HDPE geomembrane 1 and the TPO geomembrane 2 to form a combined geomembrane anti-seepage system, such as Figure 1 and Figure 2 shown. The combined geomembrane anti-seepage system includes the HDPE geomembrane 1, the TPO geomembrane 2, and the transition zone anti-seepage material 3 connecting the HDPE geomembrane 1 and the TPO geomembrane 2. And the HDPE geomembrane 1 and the TPO geomembrane 2 are connected by the transition zone anti-seepage material 3 to form at least one connection part (seam). The peel strength F1 of each connection part is greater than or equal to 6 N / mm (i.e., F1≥6 N / mm). Specifically, for each connection part, in the curve of the peel strength changing with displacement at this connection part, in the interval where the displacement exceeds 100 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm.
[0097] In the embodiments of the present invention, in the combined geomembrane anti-seepage system formed by welding the HDPE geomembrane 1 and the TPO geomembrane 2 with the above-mentioned transition zone anti-seepage material, there is a relatively large bonding strength between the HDPE geomembrane 1 and the TPO geomembrane 2 (F1≥6 N / mm, and for each seam, in the curve of the peel strength changing with displacement at this seam, in the interval where the displacement exceeds 100 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm), making it have good connection reliability. The seams of the two can adapt to deformations caused by factors such as the pressure of the water storage body or the settlement of the base layer, etc. During the service process, they are not easily pulled apart and not easily damaged, which can improve the anti-seepage reliability of the combined geomembrane anti-seepage system formed by the HDPE geomembrane 1 and the TPO geomembrane 2, and avoid problems such as seam leakage during use, thereby forming a reliable and complete anti-seepage closed system and ensuring the project quality.
[0098] In the embodiment of the present invention, the HDPE geomembrane 1 and the TPO geomembrane 2 are connected through the transition zone anti-seepage material 3. The peel strength F1 of the formed joint is greater than or equal to 6 N / mm. And for each joint, in the curve of the peel strength of the joint varying with displacement, in the interval where the displacement exceeds 100 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm. Compared with the peel strength of the weld formed by directly welding the HDPE geomembrane 1 and the TPO geomembrane 2 (≤3 N / mm) and the peel strength of the joint formed by lap joint with an adhesive (≤3 N / mm), it is significantly improved (at least doubled), which can significantly improve the anti-seepage reliability. At the same time, compared with the connection method of rigid anchoring combined with edge sealing treatment, in the embodiment of the present invention, the HDPE geomembrane 1 and the TPO geomembrane 2 are connected through the transition zone anti-seepage material 3, which belongs to non-destructive anchoring, can improve the sealing performance of the connection part (connection and anchoring part), and has the advantages of simple process and convenient operation.
[0099] In the embodiment of the present invention, the connection method of connecting the HDPE geomembrane 1 and the TPO geomembrane 2 through the transition zone anti-seepage material 3 can be welding (that is, the above connection is welding). Correspondingly, the connection part formed by welding (connecting) the HDPE geomembrane 1 and the TPO geomembrane 2 through the transition zone anti-seepage material 3 is the welding part of the two (that is, the above joint is a weld). That is to say, in the combined type geomembrane anti-seepage system, the HDPE geomembrane 1 and the TPO geomembrane 2 are welded through the transition zone anti-seepage material 3 to form at least one welding part (weld). The peel strength F1 of each welding part is greater than or equal to 6 N / mm (that is, F1≥6 N / mm). And for each welding part, in the curve of the peel strength of the welding part varying with displacement, in the interval where the displacement exceeds 100 mm, there is a curve segment where the peel strength is greater than or equal to 6 N / mm.
[0100] In the embodiment of the present invention, the welding can specifically be welding methods such as single-seam welding, double-seam welding or extrusion welding. During specific implementation, it can be selected according to needs.
[0101] In the embodiment of the present invention, a conventional single-seam welding machine in the art can be used for single-seam welding, a conventional double-seam welding machine in the art can be used for double-seam welding, and a conventional extrusion welding gun can be used for extrusion welding. For example, a Swiss Leister Varimat V hot air type automatic welding machine can be used for single-seam welding, a Swiss Leister Twinny T hot air / thermal wedge combined double-track automatic welding machine can be used for double-seam welding, and a Leister Fusion 2 handheld extrusion welding gun can be used for extrusion welding.
[0102] The embodiments of the present invention are applicable to various welding methods. Whether it is single-seam welding or double-seam welding, using the above-mentioned transition zone anti-seepage material to weld the HDPE geomembrane 1 and the TPO geomembrane 2 can make the welding strength between the HDPE geomembrane 1 and the TPO geomembrane 2 relatively large (F1≥6N / mm, and for each welding part, in the curve of the peel strength changing with displacement at this welding part, in the interval where the displacement exceeds 100mm, there is a curve segment where the peel strength is greater than or equal to 6N / mm). The welds of the two are not easily pulled apart and are not easily damaged during service, which can improve the anti-seepage reliability of the combined geomembrane anti-seepage system and avoid problems such as weld leakage during its use.
[0103] Generally, as Figure 1 and Figure 2 described above, the above-mentioned connection part (welding part) extends in the second direction y, and the second direction is basically perpendicular to the direction from the HDPE geomembrane 1 to the TPO geomembrane 2.
[0104] Specifically, the structure of the combined geomembrane anti-seepage system formed by welding the HDPE geomembrane 1 and the TPO geomembrane 2 with the transition zone anti-seepage material can be as Figure 1 shown. As described above, at least one connection part may include a first connection part 301 between the transition zone anti-seepage material 3 and the HDPE geomembrane 1, and a second connection part 302 between the transition zone anti-seepage material 3 and the TPO geomembrane 2.
[0105] Specifically, as Figure 1 shown, the first connection part 301 may be a first welding part formed by welding the transition zone anti-seepage material 3 and the HDPE geomembrane 1 (that is, after overlapping the transition zone anti-seepage material 3 and the HDPE geomembrane 1, welding the overlapping part of the two to form the first welding part), and the second connection part 302 may be a second welding part formed by welding the transition zone anti-seepage material 3 and the TPO geomembrane 2 (that is, after overlapping the transition zone anti-seepage material 3 and the TPO geomembrane 2, welding the overlapping part of the two to form the first welding part).
[0106] In the embodiments of the present invention, in the combined geomembrane anti-seepage system, the transition zone anti-seepage material 3 can be connected between the HDPE geomembrane 1 and the TPO geomembrane 2 as a transition zone anti-seepage membrane material (as Figure 1As shown in the figure, one side of the transition zone anti-seepage material 3 is connected to the HDPE geomembrane 1 to form a first connection part 301, and the other side of the transition zone anti-seepage material 3 is connected to the TPO geomembrane 2 to form a second connection part 302. That is to say, in the combined geomembrane anti-seepage system, the HDPE geomembrane 1 and the TPO geomembrane 2 are connected by the transition zone anti-seepage material 3 to form two connection parts, namely the first connection part 301 and the second connection part 302. The peel strength F1 of both the first connection part 301 and the second connection part 302 is greater than or equal to 6 N / mm respectively. And in the curve of the peel strength of the first connection part 301 varying with displacement, in the interval where the displacement exceeds 100 mm, there is a curve segment with a peel strength greater than or equal to 6 N / mm. In the curve of the peel strength of the second connection part 302 varying with displacement, in the interval where the displacement exceeds 100 mm, there is also a curve segment with a peel strength greater than or equal to 6 N / mm.
[0107] Continue to refer to Figure 1 , when connecting the transition zone anti-seepage material 3 as the transition zone anti-seepage membrane between the HDPE geomembrane 1 and the TPO geomembrane 2, the transition zone anti-seepage material 3 generally may also include a body part 300 located between the first connection part 301 and the second connection part 302. This body part 300 is the part where the transition zone anti-seepage material 3 exists alone, and it is not welded to the HDPE geomembrane 1 nor to the TPO geomembrane 2.
[0108] Specifically, when connecting the transition zone anti-seepage material 3 as the transition zone anti-seepage membrane between the HDPE geomembrane 1 and the TPO geomembrane 2 (as Figure 1 shown), the transition zone anti-seepage material 3 can be lap-welded to the HDPE geomembrane 1 and the TPO geomembrane 2 respectively. Specifically, single-seam welding or double-seam welding methods can be used to form the first connection part 301 (the first welding part) and the second connection part 302 (the second welding part).
[0109] Or, as Figure 2 shown, at least one of the above-mentioned connection parts is a third connection part 303. The third connection part 303 can be a third welding part formed by welding the HDPE geomembrane 1, the TPO geomembrane 2 and the transition zone anti-seepage material 3 (that is, after overlapping the parts to be welded of the HDPE geomembrane 1, the parts to be welded of the TPO geomembrane 2 and the transition zone anti-seepage material 3, welding the overlapping parts of the three to form the third welding part).
[0110] Specifically, the transition zone anti-seepage material 3 can be used as a sealing edge electrode at the edge of the lap joint of the HDPE geomembrane 1 and the TPO geomembrane 2 (as Figure 2As shown in the figure, at this time, the HDPE geomembrane 1 and the TPO geomembrane 2 are connected by the transition zone anti-seepage material 3 to form a third connection part, and specifically, the third connection part (the third welding part) can be formed by extrusion welding.
[0111] As Figure 2 shown, at the third connection part 303, at least part of the area of the transition zone anti-seepage material 3 covers one of the HDPE geomembrane 1 and the TPO geomembrane 2 (hereinafter referred to as the first one), and at least part of the area covers the edge of the other of the HDPE geomembrane 1 and the TPO geomembrane 2 (hereinafter referred to as the second one).
[0112] Specifically, as Figure 2 shown, the first one can be the HDPE geomembrane 1, and the second one is the TPO geomembrane 2.
[0113] Continuing to refer to Figure 2 , the HDPE geomembrane 1 and the TPO geomembrane 2 overlap, and the overlapping area of the two includes the fourth connection part 4 of the HDPE geomembrane 1 and the TPO geomembrane 2. The fourth connection part 4 can specifically be the fourth welding part formed by welding the HDPE geomembrane 1 and the TPO geomembrane 2, for example, the fourth welding part is formed by single-seam welding or double-seam welding. Among them, the first one includes a main body area on one side of the fourth connection part 4 in the first direction x, and an edge area on the other side of the fourth connection part 4 in the first direction x. The edge area overlaps on the surface of the second one, and part of the area of the transition zone anti-seepage material 3 covers the edge area, and the other part of the area covers the second one. The first one and the second one are sealed and anti-seepage reinforced by the transition zone anti-seepage material 3. Among them, the first direction x is basically parallel to the direction from the HDPE geomembrane 1 to the TPO geomembrane 2.
[0114] During specific implementation, after welding the HDPE geomembrane 1 and the TPO geomembrane 2 to form the fourth welding part, the transition zone anti-seepage material 3 (sealing edge electrode) is covered on the edge area of the first one of the HDPE geomembrane 1 and the TPO geomembrane 2 and the second one (that is, the parts to be welded of the HDPE geomembrane 1, the parts to be welded of the TPO geomembrane 2 and the transition zone anti-seepage material 3 overlap), and the overlapping parts of the three are welded to form the third welding part, so as to realize the sealing and anti-seepage reinforcement of the outer edge of the weld of the HDPE geomembrane 1 and the TPO geomembrane 2.
[0115] In the embodiments of the present invention, the peel strength between the transition zone anti-seepage material and the HDPE geomembrane 1 and the TPO geomembrane 2 (or the welding peel strength, which is also the peel strength of the connection part formed by the HDPE geomembrane 1 and the TPO geomembrane 2 through the transition zone anti-seepage material 3), and the change curve of the peel strength with displacement can be measured according to the provisions of GB / T 328.21-2007 "Test Methods for Building Waterproofing Membranes - Part 21: Seam Peel Performance of Polymer Waterproofing Membranes". Specifically, when testing the peel strength of a certain connection part, a test specimen including this connection part is cut from the combined type geomembrane anti-seepage system. In this test specimen, on both opposite sides of this connection part, appropriate widths of the HDPE geomembrane 1 and the TPO geomembrane 2 are respectively reserved (the connection part is located between the reserved HDPE geomembrane 1 and TPO geomembrane 2). Subsequently, the peel strength test is carried out on the test specimen. During the test, one side of the test specimen in the first direction x is fixed, and the geomembrane on the other side of the test specimen is clamped with a fixture and stretched outwards. The stretching speed can be 100 mm / min to measure the peel strength F1 of this connection part.
[0116] Specifically, during the test of the peel strength, a peel strength curve (i.e., the change curve of the peel strength with displacement (fixture displacement)) can be obtained.
[0117] In the embodiments of the present invention, the peel strength F1 of the said connection part refers to the maximum peel strength, that is, the maximum peel strength value (the maximum peak value) in the peel strength curve.
[0118] Specifically, for any connection part, its peel strength curve generally has at least one (one or more) peak. Correspondingly, this peel strength curve has at least one peak value (the peel strength corresponding to the highest point of the peak). When it has one peak value, the peel strength corresponding to this peak value is the maximum peel strength F1. When it has multiple peak values, the peel strength corresponding to the peak value with the maximum peel strength among these peak values is the maximum peel strength F1.
[0119] Specifically, for any connection part (such as the first connection part 301, the second connection part 302 or the third connection part 303), its peel strength curve can include one or more peak values, and the peel strengths corresponding to these peak values are all greater than or equal to 6 N / mm, and further can be greater than or equal to 8 N / mm, for example, can be greater than or equal to 10 N / mm.
[0120] In some embodiments, the peel strength curve of the first connection part 301 includes three peaks, and the peel strengths corresponding to these three peaks are all greater than or equal to 6 N / mm, further greater than or equal to 8 N / mm, and still further greater than or equal to 10 N / mm. At this time, the first connection part 301 may specifically be formed by single-seam welding the transition zone anti-seepage material 3 and the HDPE geomembrane 1.
[0121] For example, the displacements corresponding to the above three peaks may be S1, S2, and S3 respectively, where 30 mm ≤ S1 ≤ 50 mm, 70 mm ≤ S2 ≤ 100 mm, and 120 mm ≤ S3 ≤ 150 mm, but it is not limited thereto.
[0122] Specifically, the hardness of the transition zone anti-seepage material 3 may be less than the hardness of the HDPE geomembrane 1, and the hardness of the transition zone anti-seepage material 3 may be greater than the hardness of the TPO geomembrane 2. During the stretching process of the transition zone anti-seepage material 3 and the HDPE geomembrane 1, the deformation is mainly concentrated on the transition zone anti-seepage material 3. During the stretching process of the transition zone anti-seepage material 3 and the TPO geomembrane 2, the deformation is mainly concentrated on the TPO geomembrane 2. The HDPE geomembrane 1 has a yield characteristic, and deformation concentration is likely to occur at the unilateral edge of the weld and it is torn within a short distance; while the TPO geomembrane 2 has strong multi-directional deformation adaptability and uniform deformation, and deformation concentration is not likely to occur at the weld edge. Connecting the HDPE geomembrane 1 and the TPO geomembrane 2 through the transition zone anti-seepage material 3 is beneficial to conducting the deformation to the material with strong deformation adaptability in the combined geomembrane anti-seepage system of multiple geomembranes, thereby reducing the failure risk of the overall anti-seepage system and further improving the anti-seepage reliability of the combined geomembrane anti-seepage system.
[0123] In some embodiments, the hardness of the transition zone anti-seepage material 3 is between 40 and 55 Shore D.
[0124] Generally, the hardness of the HDPE geomembrane 1 is greater than or equal to 55 Shore D, and the hardness of the TPO geomembrane 2 is less than or equal to 40 Shore D.
[0125] In the embodiments of the present invention, the HDPE geomembrane 1 (high-density polyethylene geomembrane) may be a conventional HDPE geomembrane 1 in the art, and the TPO geomembrane 2 (thermoplastic polyolefin geomembrane) may be a conventional TPO geomembrane 2 in the art, and both of them can be obtained by conventional methods in the art, such as commercial purchase or self-making by conventional methods in the art, and no special limitation is made thereto.
[0126] The present invention is further introduced below through specific embodiments. In the following examples and comparative examples, unless otherwise specified, a single-seam welding is performed using a Swiss Leister Varimat V hot air automatic welder, and the temperature and speed of the single-seam hot air welder are 500 °C and 2.5 m / min, respectively; a double-seam welding is performed using a Swiss Leister Twinny T hot air / thermal wedge combined double-track automatic welder, and the temperature and speed of the double-track hot air / thermal wedge combined welder are 270 °C and 2.4 m / min, respectively.
[0127] In the following examples and comparative examples, unless otherwise specified, the metallocene medium-density polyethylene used is mPE E332H of Sinopec, the high-density polyethylene is TR144 of Sinopec, the linear low-density polyethylene is ExceedS 9243ML of ExxonMobil, the reactive TPO is Hifax CA 10A of LyondellBasell, the C3 / C2 binary copolymer polypropylene is B9302 of Sinopec, the homopolypropylene is M02d of Sinopec, the ethylene / α-octene block copolymer is Infuse9100 of Dow Chemical, the propylene / ethylene block copolymer is Intune d5535 of Dow Chemical, the calcium carbonate is Omyacarb 6 of Omya Calcium Industry, the antioxidant is Irganox B 225 of BASF, the light stabilizer is Chimassorb 2020 of BASF, the pigment (titanium dioxide) is LR-972 of Longmang Titanium Industry, the polymerized rosin is POLY-PALE of Eastman, the rosin ester is Sylvalite RE 105L of Kraton, and the hydrogenated rosin is AX-E of Eastman.
[0128] Example 1
[0129] In this Example 1, the formulation of the transition zone anti-seepage material is shown in Table 1.
[0130] Table 1 Formulation of the transition zone anti-seepage material
[0131] Raw material type Specific raw material Weight ratio Polyethylene resin Metallocene medium density polyethylene 36 parts Flexible polypropylene resin Reaction grade TPO 25 parts Olefin block copolymer resin Ethylene / α-octene block copolymer 15 parts Olefin block copolymer resin Propylene / ethylene block copolymer 8 parts Filler Calcium carbonate 10 parts Flux Polymerized rosin 1.5 parts Flux Hydrogenated rosin 1.5 parts Antioxidant Irganox B 225 0.5 part Light stabilizer Chimassorb 2020 0.5 part Pigment Titanium dioxide 2 parts
[0132] Example 2
[0133] In this Example 2, the formulation of the transition zone anti-seepage material is shown in Table 2.
[0134] Table 2 Formulation of the transition zone anti-seepage material
[0135] Raw material type Specific raw material Weight ratio Polyethylene resin Metallocene medium density polyethylene 37 parts Flexible polypropylene resin Reaction grade TPO 15 parts Flexible polypropylene resin <![CDATA[C3 / C2 binary copolymer polypropylene]]> 6 parts Olefin block copolymer resin Ethylene / α-octene block copolymer 15 parts Filler Calcium carbonate 20 parts Flux Hydrogenated rosin 4 parts Antioxidant Irganox B 225 0.5 part Light stabilizer Chimassorb 2020 0.5 part Pigment Titanium dioxide 2 parts
[0136] Example 3
[0137] In this Example 3, the formulation of the anti-seepage material for the transition zone is shown in Table 3.
[0138] Table 3 Formulation of the anti-seepage material for the transition zone
[0139] Raw material type Specific raw material Weight ratio Polyethylene resin High density polyethylene 23 parts Polyethylene resin Linear low density polyethylene 5 parts Flexible polypropylene resin Reaction grade TPO 14 parts Flexible polypropylene resin Homopolypropylene 5 parts Olefin block copolymer resin Propylene / ethylene block copolymer 15 parts Filler Calcium carbonate 30 parts Flux Rosin ester 5 parts Antioxidant Irganox B 225 0.5 part Light stabilizer Chimassorb 2020 0.5 part Pigment Titanium dioxide 2 parts
[0140] Comparative Example 1: The difference from Example 1 is that in Comparative Example 1, the anti-seepage material for the transition zone is not used, and instead, the HDPE geomembrane and the TPO geomembrane are directly connected by welding.
[0141] Comparative Example 2
[0142] In this Comparative Example 2, the formulation of the anti-seepage material for the transition zone is shown in Table 4.
[0143] Table 4 Formulation of the anti-seepage material for the transition zone
[0144] Raw material type Specific raw material Weight ratio Polyethylene resin Metallocene medium density polyethylene 40 parts Flexible polypropylene resin Reaction grade TPO 30 parts Olefin block copolymer resin Ethylene / α-octene block copolymer 18 parts Olefin block copolymer resin Propylene / ethylene block copolymer 11 parts Antioxidant Irganox B 225 0.5 part Light stabilizer Chimassorb 2020 0.5 part
[0145] Comparative Example 3
[0146] In this Comparative Example 3, the formulation of the anti-seepage material for the transition zone is shown in Table 5.
[0147] Table 5 Formulation of the anti-seepage material for the transition zone
[0148] Raw material type Specific raw material Weight ratio Polyethylene resin Linear low density polyethylene 82 parts Filler Calcium carbonate 15 parts Antioxidant Irganox B 225 0.5 part Light stabilizer Chimassorb 2020 0.5 part Pigment Titanium dioxide 2 parts
[0149] The anti-seepage materials for the transition zone of Examples 1 to 3, Comparative Example 2, and Comparative Example 3 are respectively used to weld the HDPE geomembrane and the TPO geomembrane, and the peel strength is tested.
[0150] Test Example 1
[0151] The preparation process of the homogeneous anti-seepage membrane materials for the transition zone of Examples 1 to 3, Comparative Example 2, and Comparative Example 3 is as follows: Using a high-speed mixer, the resin pellets and powders in the formulation are respectively mixed evenly, and then shear co-mixing extrusion is carried out using a twin-screw extruder, and a flat extrusion die is adopted; among them, the resin pellets are fed from the feeding port at the starting end of the screw, and the powders are fed from the side feeding port; the barrel temperature of the twin-screw extruder is set at 165 - 195 °C to ensure that the melt temperature does not exceed 230 °C; the sheet extruded from the die directly enters the three-roll calendering for thickness determination, and then goes through processes such as trimming and length determination cutting to obtain the homogeneous anti-seepage membrane material for the transition zone.
[0152] According to the following process, the peel strength of the welds (the first connection part) between the homogeneous anti-seepage membrane materials for the transition zone of Examples 1 to 3, Comparative Example 2, and Comparative Example 3 and the HDPE geomembrane is respectively tested:
[0153] (1) Welding: Cut 2 specimens of 300 mm × 200 mm (1 piece of transition zone anti-seepage membrane material and 1 piece of HDPE geomembrane), wipe the welding surface of the membrane material clean with anhydrous ethanol; on the rock wool workbench, use an automatic welder to weld the overlapping edges of the two specimens tightly, and use a hook to check for any loose welding or missed welding;
[0154] (2) Peel strength test: After the weld cools, according to the provisions of GB / T 328.21-2007 "Test Methods for Building Waterproofing Membranes - Part 21: Seam Peel Performance of Polymer Waterproofing Membranes", cut a 50 mm wide rectangular specimen for the weld peel strength and peel strength curve test, with a tensile speed of 100 mm / min.
[0155] In addition, cut 2 specimens of 300 mm × 200 mm (1 piece of transition zone anti-seepage membrane material and 1 piece of TPO geomembrane), and refer to the above welding and peel strength test procedures to test the peel strength of the welds (the second connection part) between the homogeneous transition zone anti-seepage membrane material and the TPO geomembrane in Examples 1 to 4 and Comparative Example 2 respectively;
[0156] In addition, in Comparative Example 1, cut 2 specimens of 300 mm × 200 mm (1 piece of HDPE geomembrane and 1 piece of TPO geomembrane), and refer to the above welding and peel strength test procedures to test the peel strength of the weld directly welding the HDPE geomembrane and 1 piece of TPO geomembrane. Among them, the measured peel strength of the single seam welding (single weld peel strength) of the HDPE geomembrane and 1 piece of TPO geomembrane is about 2 N / mm, and the peel strength of the double seam welding (double weld peel strength) is about 3 N / mm.
[0157] Among them, perform single seam welding according to the process of step (1), and then perform the peel strength test of step (2). The measured peel strength of the single seam welding (single weld peel strength) F1 of the transition zone anti-seepage material and the HDPE geomembrane is shown in Table 1; perform double seam welding according to the process of step (2), and then perform the peel strength test of step (2). The measured peel strength of the double seam welding (double weld peel strength) F1 of the transition zone anti-seepage material and the HDPE geomembrane is shown in Table 6.
[0158] In addition, Figure 3The peel strength curves of the single-seam welding of the transition zone anti-seepage material of Example 1 and the TPO geomembrane (Example 1 / TPO single seam), the peel strength curves of the single-seam welding of the transition zone anti-seepage material of Example 1 and the HDPE geomembrane (Example 1 / HDPE single seam), the peel strength curves of the double-seam welding of the transition zone anti-seepage material of Example 1 and the TPO geomembrane (Example 1 / TPO double seam), the peel strength curves of the double-seam welding of the transition zone anti-seepage material of Example 1 and the HDPE geomembrane (Example 1 / HDPE double seam), the peel strength curves of the single-seam welding of the HDPE geomembrane and the TPO geomembrane of Comparative Example 1 (HDPE / TPO single seam (Comparative Example 1)), and the peel strength curves of the double-seam welding of the HDPE geomembrane and the TPO geomembrane of Comparative Example 1 (HDPE / TPO double seam (Comparative Example 1)) are shown.
[0159] In addition, Figure 4 The peel strength curves of the single-seam welding of the transition zone anti-seepage material of Example 1 and the HDPE geomembrane (Example 1 / HDPE single seam) and the peel strength curves of the single-seam welding of the transition zone anti-seepage material of Comparative Example 2 and the HDPE geomembrane (Comparative Example 2 / HDPE single seam) are shown.
[0160] In addition, Figure 5 The peel strength curves of the single-seam welding of the transition zone anti-seepage material of Example 1 and the TPO geomembrane (Example 1 / TPO single seam), the peel strength curves of the double-seam welding of the transition zone anti-seepage material of Example 1 and the TPO geomembrane (Example 1 / TPO double seam), the peel strength curves of the single-seam welding of the transition zone anti-seepage material of Comparative Example 3 and the TPO geomembrane (Comparative Example 3 / TPO single seam), and the peel strength curves of the double-seam welding of the transition zone anti-seepage material of Comparative Example 3 and the TPO geomembrane (Comparative Example 3 / TPO double seam) are shown.
[0161] In addition, the Shore hardness of the transition zone anti-seepage geomembranes of Examples 1 to 3, Comparative Example 2, and Comparative Example 3 was measured, as shown in Table 6.
[0162] Table 6 Peel Strength Test Results
[0163]
[0164]
[0165] According to the test results of the peel strength and the peel strength curve, compared with Comparative Example 1, Comparative Example 2, and Comparative Example 3, in Examples 1 to 3, the peel strength F1 between the transition zone anti-seepage material and the HDPE geomembrane, and the peel strength F1 between the transition zone anti-seepage material and the TPO geomembrane both reached more than 6 N / mm. Moreover, in the curve of the peel strength of the transition zone anti-seepage material and the HDPE geomembrane varying with displacement, in the interval where the displacement exceeded 100 mm, there was a curve segment with a peel strength greater than or equal to 6 N / mm. In the curve of the peel strength of the transition zone anti-seepage material and the TPO geomembrane varying with displacement, in the interval where the displacement exceeded 100 mm, there was a curve segment with a peel strength greater than or equal to 6 N / mm (and specifically shown in Figures 3 to 6 are the peel strength curves of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3), that is, the transition zone anti-seepage material shows good welding strength whether it is with the HDPE geomembrane or the TPO geomembrane. This shows that the transition zone anti-seepage material of the embodiments of the present invention can be applied to weld the HDPE geomembrane and the TPO geomembrane, improve the welding strength of the HDPE geomembrane and the TPO geomembrane, and further improve the anti-seepage reliability of the combined type geomembrane anti-seepage system.
[0166] In addition, compared with Comparative Example 2, Examples 1 to 3 introduce components such as fillers into the transition zone anti-seepage material, which can also increase the surface roughness of the transition zone anti-seepage material, reduce its melt fluidity during the welding process, reduce the phenomenon of thinning at the weld edge, and further improve the welding reliability.
[0167] Further combined with Figure 3 and Figure 4 it can be seen that the peel strength curve of Example 1 has three peaks, and the peel strength of each peak is greater than 10 N / mm; the peel strength curve of Comparative Example 2 has a peak with a peel strength exceeding 6 N / mm, and the peel strength after the fixture displacement exceeds 20 mm is lower than 6 N / mm. The reason for the analysis is that there is a problem of local virtual welding at the welding part of Comparative Example 2, and compared with Comparative Example 2, Examples 1 to 3 show better welding reliability.
[0168] Test Example 2
[0169] The preparation process of the transition zone material for forming the edge-sealing electrode in Example 1 is as follows: Use a high-speed mixer to mix the resin pellets and powders in the formula evenly, and use a twin-screw extruder for shear blending and extrusion granulation, adopting a round-hole die; among them, the resin pellets are fed from the feeding port at the starting end of the screw, and the powders are fed from the side feeding port; the strip extruded from the die mouth is cooled by circulating water in a water tank, traction, air drying, fixed-length cutting, drying and other processes to obtain the transition zone material for forming the edge-sealing electrode; the barrel temperature of the twin-screw extruder is set at 165-195 °C to ensure that the melt temperature does not exceed 230 °C; the diameter of the electrode is controlled at about 3-4 mm by controlling the ratio of the extrusion amount to the traction speed.
[0170] According to the following process, the transition zone material of Example 1 is used to seal and weld the HDPE geomembrane and the TPO geomembrane, and the peel strength of the weld (the third connection part) is tested: Cut 2 specimens of 300 mm × 200 mm (1 piece of HDPE geomembrane and 1 piece of TPO geomembrane), and wipe the welding surface of the membrane material clean with anhydrous ethanol; Align the edges of the two specimens on the rock wool workbench, and then translate and stagger them for staggered joint stacking (as Figure 2 shown); Use a Swiss Leister Fusion2 hand-held extrusion welding gun to extrude the electrode above the staggered joint to squeeze and seal the staggered joint. After the electrode is extruded, it forms a colloidal wide strip about 50 cm long. Half of the wide strip covers the HDPE geomembrane, and the other half covers the TPO geomembrane. Use a hook to check for virtual welding and missed welding; After the weld cools, according to the provisions of GB / T328.21-2007 "Test Methods for Building Waterproofing Membranes - Part 21: Peel Performance of Polymer Waterproofing Membrane Joints", cut a rectangular specimen 50 mm wide for weld peel strength testing. The temperature of the hand-held extrusion welding gun is set at 450 °C.
[0171] The peel strength of the third connection part is measured to be about 10 N / mm (combined Figure 6 It can be seen that the peel strength of the third connection part is slightly greater than 10 N / mm). Among them, Figure 6 shows the peel strength curve corresponding to the third connection part of Example 1 (Example 1 electrode / TPO&HDPE), the peel strength curve of the single-seam welding of the HDPE geomembrane and the TPO geomembrane in Comparative Example 1 (HDPE / TPO single seam (Comparative Example 1)), and the peel strength curve of the double-seam welding of the HDPE geomembrane and the TPO geomembrane in Comparative Example 1 (HDPE / TPO double seam (Comparative Example 1)).
[0172] As can be seen from the test results, by using the transition zone material of Embodiment 1 to perform extrusion welding on the lap joint area of the HDPE geomembrane and the TPO geomembrane, the anti-seepage reliability at the joint of the HDPE and TPO geomembranes can be greatly improved. It is stated in the specification that the anti-seepage material of the transition zone in the embodiments of the present invention can be used as a welding rod for edge sealing, and is suitable for performing extrusion welding on the outer edge of the welding joint of the HDPE and TPO geomembranes to improve the anti-seepage reliability of the combined geomembrane anti-seepage system.
[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A transition zone anti-seepage material, characterized in that: The transition zone anti-seepage material meets the following requirements: In the variation curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane with displacement, there is a curve segment with a peel strength greater than or equal to 6N / mm in the interval where the displacement exceeds 30mm; In the curve of variation of the welding peel strength of the transition zone anti-seepage material and the TPO geomembrane with displacement, there is a curve segment with a peel strength greater than or equal to 6 N / mm in the interval where the displacement exceeds 30 mm.
2. The transition zone anti-seepage material according to claim 1, characterized in that: In the variation curve of the welding peel strength of the transition zone anti-seepage material and the HDPE geomembrane with displacement, there is a curve segment with a peel strength greater than or equal to 6N / mm in the interval where the displacement exceeds 50mm; And / or, in the curve of variation of welding peel strength between the transition zone anti-seepage material and the TPO geomembrane as a function of displacement, there is a curve segment with a peel strength greater than or equal to 6 N / mm in an interval where the displacement exceeds 50 mm.
3. The transition zone anti-seepage material according to claim 1, characterized in that: The transition zone anti-seepage material comprises a resin film layer, wherein the resin film layer comprises polyethylene resin, polypropylene resin, olefin block copolymer resin, filler and soldering flux, and the soldering flux comprises rosin-based material.
4. The transition zone anti-seepage material according to claim 3, characterized in that: The mass ratio of the polyethylene resin to the resin film layer is 25%-60%; And / or, the mass ratio of the polypropylene resin to the resin film layer is 12%-38%; And / or, the mass ratio of the olefin block copolymer resin to the resin film layer is 4%-26%; And / or, the mass ratio of the filler to the resin film layer is 10% to 40%; And / or, the mass ratio of the soldering flux to the resin film layer is 0.1% to 8%; And / or, the polyethylene resin includes one or more of high-density polyethylene, medium-density polyethylene, and linear low-density polyethylene; And / or, the density of the polyethylene resin is 0.920-0.955 g / cm 3 The melt index at 190℃ and 2.16KG is between 0.15-4.0g / 10min; And / or, the polypropylene resin includes one or more of propylene / ethylene / butene terpolymer polypropylene, propylene / ethylene binary copolymer polypropylene, and homopolymer polypropylene; And / or, the density of the polypropylene resin is 0.850-0.930 g / cm 3 The melt index at 230℃ and 2.16KG is between 0.3-3.5g / 10min; And / or, the olefin block copolymer resin includes one or more of ethylene / α-octene block copolymer and propylene / ethylene block copolymer; the density of the ethylene / α-octene block copolymer is 0.860-0.890 g / cm 3 The melt index at 190°C and 2.16KG is between 0.3-5.0; the density of the propylene / ethylene block copolymer is between 0.870-0.910 g / cm 3 The melt index at 230℃ and 2.16KG is between 6.0-10.0; And / or, the filler includes one or more of calcium carbonate, talc, calcined kaolin, and calcite; And / or, the rosin material includes one or more of polymerized rosin, rosin ester, and hydrogenated rosin; The transition zone anti-seepage material is the resin film layer, or the transition zone anti-seepage material further includes a support layer composited with the resin film layer, and the support layer includes non-woven fabric and / or mesh fabric.
5. The transition zone anti-seepage material according to claim 3 or 4, characterized in that: The resin film layer also includes an antioxidant, a light stabilizer and a pigment. In parts by mass, the mass parts of the components of the resin film layer are as follows: 25-60 parts of the polyethylene resin, 12-38 parts of the polypropylene resin, 4-26 parts of the olefin block copolymer, 10-40 parts of the filler, 0.1-8 parts of the flux, 0.1-2 parts of the antioxidant, 0.1-2 parts of the light stabilizer, and 0.1-5 parts of the pigment.
6. The transition zone anti-seepage material according to claim 5, characterized in that: The antioxidant includes organic phosphite and / or hindered phenol antioxidant; and / or, the light stabilizer comprises a hindered amine light stabilizer; And / or, the pigment includes one or more of titanium dioxide, carbon black, iron oxide, Prussian blue, lead silicate, monoazo, disazo, and phthalocyanine.
7. The transition zone anti-seepage material according to any one of claims 1 to 4, characterized in that: The hardness of the transition zone anti-seepage material is less than the hardness of the HDPE geomembrane, and the hardness of the transition zone anti-seepage material is greater than the hardness of the TPO geomembrane; and / or the hardness of the transition zone anti-seepage material is between 40-55 Shore D; And / or, the transition zone anti-seepage material is an edge-sealing welding rod, or a transition zone anti-seepage membrane.
8. A method for preparing the transition zone anti-seepage material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: extruding a material for forming a resin layer to form a resin layer, thereby obtaining the transition zone anti-seepage material.
9. The method for preparing the transition zone anti-seepage material according to claim 8, characterized in that: The process of extruding the material for forming the resin layer comprises: extruding the material for forming the resin layer through a twin-screw extruder to form a resin layer, thereby obtaining a transition zone anti-seepage material; or, the process of extruding the material for forming the resin layer comprises: extruding and granulating the material for forming the resin layer through a twin-screw extruder, and then extruding the obtained granules through a single-screw extruder to form a resin layer, thereby obtaining a transition zone anti-seepage material; And / or, the transition zone anti-seepage material also includes a support layer composited with the resin layer, and the support layer includes non-woven fabric and / or mesh fabric; the preparation process of the transition zone anti-seepage material also includes a process of composited the resin layer with the support layer.
10. Use of the transition zone anti-seepage material according to any one of claims 1 to 7 in welding HDPE geomembranes and TPO geomembranes.
Citation Information
Patent Citations
High-welding strength TPO (Thermoplastic Polyolefin) waterproof roll and preparation method thereof
CN104194114A
TPO waterproof coil with high weld strength and preparation method thereof
CN106346941A
Aging-resistant easy-welding thermoplastic polyolefin waterproof roll material and preparation method thereof
CN107973993A
Manufacturing method of thermoplastic polyolefin waterproof coiled material
CN110480862A
Flexible geomembrane and preparation method thereof
CN111117034A